(untitled) (Praxis Educativa, 2023)
The problems linked to the training trajectories of those who enter the university are not limited to social issues, personal history or the mere transition between levels, but have strong institutional conditioning factors. This paper questions the devices that national universities have designed to regulate access to the level. The objective is to present a mapping of these devices in the national universities in Argentina built from a comparative perspective. A survey of institutional regulations was carried out, as well as information available on the official website of the institutions. After the construction of a systematized data matrix, trends are identified from a cross-sectional reading of the constructed map. There is a high presence of regulatory devices for admission in national universities, with variable characteristics regarding their mode of organization, curricular components, duration and planned evaluation methodology.